THE ROLE OF TEACHERS IN DESIGNING CREATIVE LEARNING WITH A DEEP LEARNING APPROACH AT ELEMENTARY SCHOOL LEVEL - Harahap, Nenni Hairani; Imran, Ali; Hamka; Lubis, Rosmanila (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Learning in the 21st century requires teachers to act not only as conveyors of information but also as designers of creative learning that is relevant to students' needs. The application of a deep learning approach is believed to improve critical thinking skills, in-depth conceptual understanding, and collaborative skills, which are crucial in facing the challenges of the independent curriculum. In this context, the role of teachers in the West Angkola District Teacher Working Group (KKG) is crucial to examine, particularly in designing creative learning oriented toward developing higher-order thinking skills. This study aims to analyzea the role of teachers in designing creative learning based on deep learning and explore the strategies used to integrate deep learning principles into learning planning and practice. The method used is descriptive qualitative, with data collection through observation, in-depth interviews, and documentation studies involving teachers who are members of the West Angkola District KKG.The results indicate that teachers play a strategic role in designing creative learning through the use of interactive media, developing problem-based activities, and implementing collaborative learning models. Teachers also strive to foster students' critical thinking skills through structured discussions, explorations, and reflections. The learning design implemented has been proven to not only increase student motivation but also strengthen teachers' professional competence in managing more meaningful learning. Thus, it can be concluded that the role of teachers in designing creative learning using a deep learning approach significantly contributes to the quality of the learning process in elementary schools. The results of this study are expected to serve as a reference in developing creative learning practices based on deep learning in the Teachers' Working Group (KKG) and other teacher professional development forums.